WHEN ENGLISH TEACHERS INCORPORATE THE NOTION OF RELIGIOUS MODERATION - Irwansyah, Dedi; Andianto, Andianto (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Religious moderation has received increased attention in Indonesian Islamic educational context. Despite the massive incorporation of religious moderation into various teaching contexts, the English teaching context still remains less explored. This paper is aimed at exploring what happens to English teachers when they contextualize such four pillars of religious moderation as national commitment, tolerance, anti-violence, and local culture accommodation into their English language instruction. Following a narrative inquiry, the paper presents the narrations of four English teachers of Islamic boarding schools in the Province of Lampung, Indonesia, pertaining to the integration of religious moderation pillars in English language teaching. The teachers were recruited through the scheme of a convenience purposive sampling. Research data are drawn from questionnaire and a semi-structured interview with teachers. Research findings show that the notion of religious moderation is best incorporated into supplementary teaching materials and the teaching milieu. Vocabulary building, classroom routine, public speaking activity, English competition, and the use of local text are among the plausible schemes for integrating religious moderation in English instruction at Islamic schools. Other potential schemes include curriculum development, content-based instruction, and theme-based language instruction. This study suggests English teacher’s role model to optimize the religious moderation integration